A century of human interventions on sediment flux variations in the Danube-Black Sea transition zone - Constantinescu, Adriana Maria; Tyler, Andrew N.; Stanica, Adrian; Spyrakos, Evangelos; Hunter, Peter D.; Catianis, Irina; Panin, Nicolae (Frontiers in Marine Science, 2023)
Many deltas around the world have recorded a decreasing sediment input, mostly due to retention in dams constructed on the river or in the river basin. The Danube River has recorded a significant decrease of its sediment supply to the Danube Delta and the NW Black Sea. This study uses 210Pb and 137Cs dating, to investigate the effects of the decreasing sediment flux in lakes, lagoons, delta front and prodelta area. Both the effects of the Iron Gate I and II dams and other local factors are discussed. These results define the period of 1960-1990 as the ‘major anthropic interventions period’ in the Danube Delta. Results show a decrease in siliciclastic flux, especially in lakes, the Sahalin lagoon and the prodelta area and a general increase in the Musura lagoon and the delta front area. Sand content is also shown to decrease in most areas and is replaced by silt. The changes in sediment accumulation rates depend mostly on the hydrological connectivity of the area and the local hydrotechnical works. Overall, the local anthropic interventions in the delta affect sediment flux in the subaerial delta and the delta front, while the prodelta is affected by the overall decrease caused by interventions in the river basin. This study can contribute to improving management strategies in the area and to a better understanding of future research needs in the Danube Delta-Black Sea system.